PENANAMAN KARAKTER RELIGIUS ANAK USIA DINI DALAM FILIM ANIMASI NUSSA DAN RARA - Istifarriana, Deva Mega; Kurniawan, Heru; Kasmiati, Kasmiati (Universitas Hamzanwadi, 2021)
Nussa and Rara are films that are favored by early childhood. One of the characteristics of this animated film is a religious character played by its characters. To that end, the purpose of the study was to discover, identify, and analyze the religious characters that Nussa and Rara instilled in early childhood. Research is conducted by literature studies or library research by examining libraries in the form of FIlm Animation Nussa and Rara. The result of the research is the religious character of early childhood in the animated film Nussa and Rara is played by the characters through an attitude of help, faith and fear, gratitude, and sincerity. This religious character attitude is what nussa and rara animated films instill in early childhood. By watching Nussa and Rara animated films continuously, this religious character will be internalized in early childhood.